2017
DOI: 10.1038/s41598-017-09229-7
|View full text |Cite
|
Sign up to set email alerts
|

Simple MD-based model for oxidative folding of peptides and proteins

Abstract: Significant strides have been recently made to fold peptides and small proteins in silico using MD simulations. However, facilities are currently lacking to include disulfide bonding in the MD models of protein folding. To address this problem, we have developed a simple empirical protocol to model formation of disulfides, which is perturbation-free, retains the same speed as conventional MD simulations and allows one to control the reaction rate. The new protocol has been tested on 15-aminoacid peptide guanyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…The energies of the resulting conformers were evaluated by means of the sander program from AmberTools using the Amber ff14SB force field and implicit solvent (option igb ¼ 8) (61). The obtained data were then used to construct the energy histogram, resulting in a bell-shaped distribution (62). The initial pep N H4 structure was chosen in a random manner from among 215 structures in the central part of this histogram.…”
Section: Simulationsmentioning
confidence: 99%
“…The energies of the resulting conformers were evaluated by means of the sander program from AmberTools using the Amber ff14SB force field and implicit solvent (option igb ¼ 8) (61). The obtained data were then used to construct the energy histogram, resulting in a bell-shaped distribution (62). The initial pep N H4 structure was chosen in a random manner from among 215 structures in the central part of this histogram.…”
Section: Simulationsmentioning
confidence: 99%
“…This decision is made using the rejection sampling strategy with p 0 set to 0.1 (i.e. the decision is random with the probability of positive outcome 0.1) 92 . If the outcome is negative, the scanning of the frames continues.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, it was shown that the cis / trans isomerization of N-methylated cyclic hexapeptides cannot be reliably predicted [109]. Recently, simulation of guanylin (a 15-residue peptide with four cysteines) showed that the distribution of three disulfide-bond isomers is in qualitative agreement with experiment, but the most stable conformation of the isomer 2 is significantly different from the poorly ordered structure of the truncated peptide [110]. In another study, BE-META simulations were performed on five cyclic isoDGR-containing α/β-peptides using eight widely used force fields with explicit water to reproduce 79 NMR observables [111].…”
Section: Peptide Structure Predictionmentioning
confidence: 99%